Pakistan : 2017 Article IV Consultation-Press Release; Staff Report; Informational Annex; and Statement by the Executive Director for Pakistan. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights that Pakistan's outlook for economic growth is favorable. Real GDP is estimated at 5.3 percent in FY2016/17 and strengthening to 6 percent over the medium term on the back of stepped-up China Pakistan Economic Corridor investments, improved availability of energy, and growth-supporting structural reforms. Inflation has been gradually increasing but remains contained, and the financial sector has remained sound. Key external risks include lower trading partner growth, tighter international financial conditions, a faster rise in international oil prices, and over the medium term, failure to generate sufficient exports to meet rising external obligations from large-scale foreign-financed investments.